Improvement of the probiotic potential and yield of Lactobacillus rhamnosus cells using corn steep liquor. (September 2020) - Wu, Wanqin; Pang, Bing; Yang, RongRong; Liu, Guanwen; Ai, Chongyang; Jiang, Chunmei; Shi, Junling
Abstract: Cultivation of Lactobacillus rhamnosus using corn steep liquor provides an attractive method for comprehensive use of the major byproduct of the corn starch industry and low cost to produce probiotics. However, most L. rhamnosus strains can not grow well at high concentration of corn steep liquor. In this study, a strain that can grow well in 500 mg⋅L −1 corn steep liquor was obtained after a continuous domestication of L. rhamnosus SHA113 in the medium containing gradually increased corn steep liquor concentration. Besides of keeping similar high antioxidant activity, antibacterial activity, and resistance to antibiotics to the original strain, the domesticated strain showed relatively better probiotic potential, such as faster growth profile and stronger resistance to acids, bile salts, lysozyme, and 0.4% phenol, and higher production of biofilms and extracellular polysaccharides. After response surface analysis, the highest yield of the domesticated strain cells (9.78 × 10 10 cfu⋅mL −1 ) was obtained at the optimal medium compositions of glucose 10.96 g⋅L −1, peptone 0.86 g⋅L −1, yeast extract 12.17 g⋅L −1, and corn steep liquor 435.4 mL⋅L −1 in a newly developed multilayer reactor. Overall, the study developed an efficient way to enhance the probiotic potential and the yield of L. rhamnosus cells using corn steep liquor. Highlights: Domestication in corn steep liquor enhanced the probiotic actives of L. rhamnosus . Domesticated strain showed high yields in corn steep liquor medium. A multilayer reactor was developed for L. rhamnosus cultivation. Optimal conditions for cultivation of L. rhamnosus in corn steep liquor were obtained.